Healthcare workers' views on mandatory SARS-CoV-2 vaccination in the UK: A cross-sectional, mixed-methods analysis from the UK-REACH study. (April 2022) - Woolf, Katherine; Gogoi, Mayuri; Martin, Christopher A.; Papineni, Padmasayee; Lagrata, Susie; Nellums, Laura B.; McManus, I.Chris; Guyatt, Anna L.; Melbourne, Carl; Bryant, Luke; Gupta, Amit; John, Catherine; et al.
Summary: Background: Several countries now have mandatory SARS-CoV-2 vaccination for healthcare workers (HCWs) or the general population. HCWs' views on this are largely unknown. Using data from the nationwide UK-REACH study we aimed to understand UK HCW's views on improving SARS-CoV-2 vaccination coverage, including mandatory vaccination. Methods: Between 21st April and 26th June 2021, we administered an online questionnaire via email to 17 891 UK HCWs recruited as part of a longitudinal cohort from across the UK who had previously responded to a baseline questionnaire (primarily recruited through email) as part of the United Kingdom Research study into Ethnicity And COVID-19 outcomes in Healthcare workers (UK-REACH) nationwide prospective cohort study. We categorised responses to a free-text question "What should society do if people do not get vaccinated against COVID-19?" using qualitative content analysis. We collapsed categories into a binary variable: favours mandatory vaccination or not, using logistic regression to calculate its demographic predictors, and its occupational, health, and attitudinal predictors adjusted for demographics. Findings: Of 5633 questionnaire respondents, 3235 answered the free text question. Median age of free text responders was 47 years (IQR 36–56) and 2705 (74.3%) were female. 18% ( n  = 578) favoured mandatory vaccination (201 [6%] participants for HCWs and others working with vulnerable populations; 377 [12%] for the general population), but the most frequent suggestion was education (32%, n  = 1047). Older HCWs (OR 1.84; 95% CI 1.44–2.34 [≥55 years vs 16 years to <40 years]), HCWs vaccinated against influenza (OR 1.49; 95% CI 1.11–2.01 [2 vaccines vs none]), and with more positive vaccination attitudes generally (OR 1.10; 95% CI 1.06–1.15) were more likely to favour mandatory vaccination, whereas female HCWs (OR= 0.79, 95% CI 0.63–0.96, vs male HCWs) and Black HCWs (OR=0.46, 95% CI 0.25–0.85, vs white HCWs) were less likely to. Interpretation: Only one in six of the HCWs in this large, diverse, UK-wide sample favoured mandatory vaccination. Building trust, educating, and supporting HCWs who are hesitant about vaccination may be more acceptable, effective, and equitable. Funding: MRC-UK Research and Innovation grant (MR/V027549/1) and the Department of Health and Social Care (DHSC) via the National Institute for Health Research (NIHR). Core funding was also provided by NIHR Biomedical Research Centres.